Analysis of Consumer Preferences at Organic Food Purchase in Romania - Vietoris Vladimír; Kozelová Dagmar; Mellen Martin; Chreneková Marcela; Potclan Janko E.; Fikselová Martina; Kopkáš Peter; Horská Elena (Polish Journal of Food and Nutrition Sciences)
The decision-making process of consumers buying organic food is affected by several factors. Because of organic agriculture in Romania is growing, the objective of this paper was to analyze consumer opinions and preferences concerning organic food products in Romania. The survey involved 350 respondents. The respondents were divided into two groups using the Hierarchical multiple factor analysis (HMFA). The strongest reason for buying organic food for Romanian respondents is health care, presented by 42% of respondents. Respondents prefer to buy organic foods directly from the producers, followed by supermarkets, specialized shops and pharmacies. The prevailing price of monthly purchase of organic food is 10 to 20€. The respondents are able to pay for organic food from 5 to 10% more than for conventional food.